Implicit Association Test (IAT) studies investigating pitch-shape audiovisual cross-modal associations across language groups - Shang, Nan (2023)
Previous studies have shown that Chinese speakers and non-Chinese speakers exhibit different patterns of cross-modal congruence for the lexical tones of Mandarin Chinese, depending on which features of the pitch they attend to. But is this pattern of language-specific listening a conscious cultural strategy or an automatic processing effect? If automatic, does it also apply when the same pitch contours no longer sound like speech? Implicit Association Tests (IATs) provide an indirect measure of cross-modal association. In a series of IAT studies, conducted with participants with three kinds of language backgrounds (Chinese-dominant bilinguals, Chinese balanced bilinguals, and English speakers with no Chinese experience) we find language-specific congruence effects for Mandarin lexical tones but not for matched sine-wave stimuli. That is, for linguistic stimuli, non-Chinese speakers show advantages for pitch-height congruence (high-pointy, low-curvy); no congruence effects were found for Chinese speakers. For non-linguistic stimuli, all participant groups showed advantages for pitch-height congruence. The present findings suggest that non-lexical tone congruence (high-pointy, low-curvy) is a basic congruence pattern, and the acquisition of a language with lexical tone can alter this perception.